Implementation of Palliative Care in Reducing Hospital Readmission Among Cancer Patients: A Systematic Review - Rifqi Alifa Bestari; Tuti Nuraini; Allenidekania Allenidekania (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Cancer patients are a population at high risk of hospital readmissions due to complex symptoms. Palliative care is a multidisciplinary approach that has the potential to reduce these readmissions by providing comprehensive support.This systematic review aimed to systematically assess palliative care interventions in reducing hospital readmission among cancer patients.A systematic literature search was conducted across six major databases (PubMed, Scopus, ScienceDirect, ClinicalKey Nursing, JSTOR, and SAGE Journals) using keywords including “cancer patients”, “palliative care”, and “hospital readmission”. Inclusion criteria encompassed quantitative studies that assessed the impact of palliative care interventions on hospital readmission rates. The methodological quality of each study was appraised using the appropriate JBI Critical Appraisal Tools.Out of 10,565 original records, 8 studies were included. The study looked into both inpatient and home care-based interventions. Results consistently showed that between 7 and 30 days after discharge, palliative care significantly decreased the readmission rate.Palliative care is effective in reducing hospital readmission among cancer patients. Keywords: Hospital Readmission, Palliative Care, Cancer Patients.